Implementation Of Islamic Values and Kemuhamadiyahan In Forming The Social Character and Leadership Of Students - Hidayaturrokhman Hidayaturrokhman; Mahsun Jayadi; Muhammad Fazlurrahman Hadi (Jurnal Ilmu Sosial Mamangan, 2024)
Al-Islam and Kemuhammadiyahan curriculum are very important for enhancing iman. The Curiculum of Al-Islam and Kemuhammadiyahan emphasize a number of subjects related to Islam that students should study. It is expected that in addition to having general knowledge and skills, they should also have character in order to become productive and hardworking individuals. This study focuses on how the Al-Islam and Kemuhammadiyahan curriculum develop social and leadership skills in students with the goal of fostering an Islamic spirit via action. Al-Islam and Kemuhammadiyahan curriculum are used to develop social and leadership skills in students. This research is intended to characterize existing phenomena, whether they are produced by human engineering or naturally; so, it is referred to as Field Research. Utilizing observations, documentation, and interview are methods for gathering data. Data analysis is conducted using inductive methodology. Analyses include data reduction, data analysis, and drawing conclusions.